Nghiên cứu lý thuyết tương tác giữa SiHF3 và NH3, CO2, CO, HCN. - Trung và cộng sự, Nguyễn Tiến (Vietnam Journal of Chemistry, 2014)
Optimized geometries are displayed in Fig. 1. Interaction energies of all examined complexes with ZPE correction range from -0.62 to -2.13 kcal.mol-1 at the MP2(full)/6-31++G(2d,2p) level. All complexes are strengthened by van der Waals interaction that is both due to Atoms in Molecules (AIM) analysis and quite small magnitude of interaction energy. All Si-H bond lengths are slightly contracted and their stretching frequencies are shifted to blue compared to the SiHF3 monomer. It is remarkable that the blue shift is still observed in the complexes possessing van der Waals weak interaction.